Chromosomes of the marine prawn, Metapenaeus affinis (H. Milne Edward) - Lakra, W S (Indian Journal of Fisheries, 2011)
A chromosomal study was conducted on the commercially important marine prawn, Metapenaeus affinis. The metaphase spreads were prepared from the postlarvae. The species possessed a modal diploid number of 2n=88 chromo -somes, NF = 116. The karyotype comprised of 9 metacentric, 5 submetacentric, 5 subtelocentric and 25 acrocentric pairs. The size of the chromosomes ranged from 0.30 to 5.46 urn. Sex chromosomes were cytologically indistinguishable